2014
DOI: 10.1021/jp502748a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Gold Cover Layer on the Encapsulation of Rhodium by Titanium Oxides on Titanium Dioxide(110)

Abstract: The present study focuses on the thermal behavior of continuous rhodium thin films (∼10 nm) deposited on a TiO 2 (110) substrate at 300 K and covered by a continuous ultrathin gold film (∼1 nm), applying scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and low-energy ion scattering (LEIS) techniques. This arrangement facilitated a rather clear-cut investigation into the effect of the Au cover layer on the wellknown encapsulation/decoration of Rh by TiO x , since the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
1
5
0
4
Order By: Relevance
“…The absence of encapsulation, and Au(111) termination of the nanoparticles at this higher Au concentration is in line with our expectations. It is also consistent with earlier work where it was reported that a thick layer of Au covering Rh nanoparticles on TiO 2 (110) hinders the diffusion of Ti and O species onto the top facet up to ~ 900 K [ 32 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The absence of encapsulation, and Au(111) termination of the nanoparticles at this higher Au concentration is in line with our expectations. It is also consistent with earlier work where it was reported that a thick layer of Au covering Rh nanoparticles on TiO 2 (110) hinders the diffusion of Ti and O species onto the top facet up to ~ 900 K [ 32 ].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, a Au overlayer on a VIII. B metal can strongly hinder the SMSI process [ 31 , 32 ], while alloy formation at higher temperatures can also occur [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work on this system was performed by Kiss,Óvári and coworkers. [4][5][6][7] Using either chemical or physical preparation techniques, they showed that Au tends to cover the Rh surface. Using scanning transmission electron microscopy (STEM), Chantry et al 8,9 highlighted the tendency of Rh either to deposit in an uneven way on Au nanorods and/or to form mixed alloy layers at the topmost surface depending on kinetic issues during the formation of such nanostructures.…”
mentioning
confidence: 99%
“…Although several groups have succeeded in synthesizing solid-solution nanoalloys of bulk-immiscible elements using colloidal methods 11 13 14 , these structures are generally metastable and cannot resist the thermal treatment needed for removing the stabilizing agents. As the thermodynamic properties of bulk alloys can influence the structure of their nanosized counterparts, some of us have recently compared the well-known bulk-miscible Au-Pd system 7 12 16 to the rarely studied bulk-immiscible Au-Rh system 11 13 17 in terms of mixing behaviour and reactivity at the nanoscale 9 15 18 . As seen for 3 nm-sized nanoparticles (NPs) anchored on well-defined rutile titania nanorods, Au and Pd atoms form a solid-solution alloy, whilst Au and Rh atoms segregate into single-phase domains within the NPs 15 .…”
mentioning
confidence: 99%